2018
DOI: 10.14740/gr1097
|View full text |Cite
|
Sign up to set email alerts
|

Liver Metastasis of Hepatoid Colonic Adenocarcinoma: A Rare and Unusual Entity With Poor Prognosis and Review of the Literature

Abstract: Hepatoid adenocarcinoma (HAC) is rare and was first reported as α-fetoprotein (AFP)-producing tumor. It is an important variant of extrahepatic adenocarcinoma with clinicopathological presentation mimicking hepatocellular carcinoma and carries exceedingly poor prognosis. HAC most commonly originates in the stomach, and less commonly in the ovary, esophagus, lung, among other organs. HAC originating in the colon is exceedingly rare. Here we report such a case of a 63-year-old man presented as decompensated live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…23 In contrast, Hu et al reported a case of GLP3-positive colonic adenocarcinoma with a poor prognosis. 24 In the present study, GLP3-positive CRCs had a poor prognosis. In addition, we found that AFP was the rarest marker (eight of 971 cases, 0.82%) among three enteroblastic markers.…”
Section: Discussionsupporting
confidence: 46%
“…23 In contrast, Hu et al reported a case of GLP3-positive colonic adenocarcinoma with a poor prognosis. 24 In the present study, GLP3-positive CRCs had a poor prognosis. In addition, we found that AFP was the rarest marker (eight of 971 cases, 0.82%) among three enteroblastic markers.…”
Section: Discussionsupporting
confidence: 46%
“…The liver is the first and most common organ to which cancers commonly metastasize and spread in patients. Recent studies have demonstrated the higher expression of SATB2 in the HCC tissues compared with adjacent normal tissues . The commonly used markers for the HCC include metastatic carcinomas markers cytokeratins (CK7, CK19 and CK20), neuroendocrine markers (CD56, synaptophysin and chromogranin A) and tissue‐specific markers (SATB2, CDX2, TTF‐1, GCDFP‐15, mammaglobin, etc) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the higher expression of SATB2 in the HCC tissues compared with adjacent normal tissues. 25,26,53,54 The commonly used markers for the HCC include metastatic carcinomas markers cytokeratins (CK7, CK19 and CK20), neuroendocrine markers (CD56, synaptophysin and chromogranin A) and tissue-specific markers (SATB2, CDX2, TTF-1, GCDFP-15, mammaglobin, etc). 54 microRNAs (miRNAs) regulate cancer cell progression and metastasis by modulating the expression of SATB2.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al reported a case of metastatic colorectal adenocarcinoma with hepatoid features of the liver which was positive for GPC3. 29 Therefore, GPC3 may not only be useful to diagnose CAED, but could also be suggestive of metastatic colorectal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%